2009
DOI: 10.1007/s10531-009-9715-2
|View full text |Cite
|
Sign up to set email alerts
|

Provision of ecosystem services by large scale corridors and ecological networks

Abstract: Large scale landscape transformation and contingent habitat loss are among the greatest threats to ecological integrity and ecosystem health. One of the mitigation approaches used to deal with these pressures is to leave interconnected corridors and nodes as remnant ecological networks (ENs) within the transformed landscape. The South African forestry industry has already allocated 500,000 ha, one-third of the plantation holdings, consisting predominantly of natural grassland, as ENs among and within timber pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 34 publications
0
50
0
1
Order By: Relevance
“…This measure can also be used in ecological networks, i.e. large-scale corridors that connect habitat patches for dispersal (Samways et al, 2010): these networks create new edges and it is relevant to know the depth of edge effect on the targeted species in order to design the corridors (Pryke and Samways, 2012). For example, Dixo and Metzger (2009) showed that too narrow corridors may prevent leaf-litter lizards from recolonizing forest fragments.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…This measure can also be used in ecological networks, i.e. large-scale corridors that connect habitat patches for dispersal (Samways et al, 2010): these networks create new edges and it is relevant to know the depth of edge effect on the targeted species in order to design the corridors (Pryke and Samways, 2012). For example, Dixo and Metzger (2009) showed that too narrow corridors may prevent leaf-litter lizards from recolonizing forest fragments.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…A specific example of the application of the FESP approach to biodiversity conservation and Ecosystem Service provision is provided by Samways et al (2010). These authors focus on the forestry industry in large-scale ecological networks in South Africa, and provide a model that elaborates on the broad framework of Fig.…”
Section: Erecting a Frameworkmentioning
confidence: 99%
“…Bennet (1999) and Hannah et al (2007) have pointed out the shortcomings of biodiversity conservation systems based on reserves alone. Now, the policies of isolated site-based conservation that developed over the last century are being replaced by planning and policy with a focus on spatial networking (see Samways et al 2010). Ecological networks that link PAs via habitat corridors, green veining and greenways are together considered a more effective approach to biodiversity conservation as they should reduce species extinction risks by facilitating movement of organisms through the landscape (Jongman and Pungetti 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These changes would severely impact numerous aspects of the natural environment, such as biodiversity and ecosystems, soils, freshwater water, and marine resources as well as human activities, such as agriculture, tourism, transport, and energy production [11]. A second driver of change is land use, which changes and fragmentation are severely impacting the environment, with habitat losses from development that cannot be offset by the creation of protected areas [12], maintenance of connectivity, ecological corridors [13], or extensive agriculture. Finally, the UN's latest projections [14] suggest that the global population will reach between 9.4 and 10 billion by 2050 (key finding 2, p. 8).…”
Section: Introductionmentioning
confidence: 99%